Aluminum Nitride SAW Resonators - Mojdeh, Ali (University of Waterloo, 2017)
Numerous devices need filters for capturing signals and then conditioning them in communications and wireless systems. For several decades, microwave filters have been the center of attention for this type of signal conditioning. However, acoustic filters have recently been gaining attention, mainly because of their miniature size and high quality factor. Among the various different types of acoustic filters, SAW filters with only metal layers on top of the piezoelectric substrate are studied in this work. The piezoelectric material used in this thesis is aluminum nitride, which exhibits a higher quality factor in SAW resonators compared to lithium niobate or other piezoelectric materials. An extensive analysis of SAW structures is carried out here, along with an investigation into the relationship between physical dimensions, piezoelectric properties and filter specifications. The proposed design procedure is followed, after which the design is verified by simulation tools such as COMSOL and Coventorware, several prototype units for resonators and filters are fabricated through MEMSCAP. The tests were performed at the Center for Integrated RF Engineering (CIRFE) lab at the University of Waterloo, Waterloo, Ontario, Canada. The Q factor of the designed aluminum nitride resonator was proven to be higher than that of lithium niobate resonators. The results obtained demonstrate the feasibility of realizing aluminum nitride-based SAW resonators using a commercially available fabrication process from MEMSCAP.
Keywords: SAW; Resonator; Aluminum Nitride; PiezoMUMPs; Mechanical Resonator